Improved biomechanical and biological outcomes in the MRL/MpJ murine strain following a full‐length patellar tendon injury. Issue 11 (25th May 2015) - Lalley, Andrea L.; Dyment, Nathaniel A.; Kazemi, Namdar; Kenter, Keith; Gooch, Cynthia; Rowe, David W.; Butler, David L.; Shearn, Jason T.
ABSTRACT Musculoskeletal injuries greatly affect the U.S. population and current clinical approaches fail to restore long‐term native tissue structure and function. Tissue engineering is a strategy advocated to improve tendon healing; however, the field still needs to establish biological benchmarks for assessing the effectiveness of tissue‐engineered structures. Investigating superior healing models, such as the MRL/MpJ, offers the opportunity to first characterize successful healing and then apply experimental findings to tissue‐engineered therapies. This study seeks to evaluate the MRL/MpJ's healing response following a central patellar tendon injury compared to wildtype. Gene expression and histology were assessed at 3, 7, and 14 days following injury and mechanical properties were measured at 2, 5, and 8 weeks. Native patellar tendon biological and mechanical properties were not different between strains. Following injury, the MRL/MpJ displayed increased mechanical properties between 5 and 8 weeks; however, early tenogenic expression patterns were not different between the strains. Furthermore, expression of the cyclin‐dependent kinase inhibitor, p21, was not different between strains, suggesting an alternative mechanism may be driving the healing response. Future studies will investigate collagen structure and alignment of the repair tissue and characterize the complete healing transcriptome to identify mechanisms driving the MRL/MpJ response. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1693–1703, 2015.